2018
DOI: 10.1002/dev.21771
|View full text |Cite
|
Sign up to set email alerts
|

Paternal line effects of early experiences persist across three generations in rhesus macaques

Abstract: The effects of early stress may not be limited to the exposed generation, but are sometimes passed on to subsequent generations. Such non-genetic transgenerational inheritance is a potentially important developmental and evolutionary force. We compared the transgenerational effects of maternal and paternal line early stress on anxiety- and health-related traits in three non-exposed generations (F1, F2 and F3) of semi-naturalistically raised rhesus macaques. As infants, F0 macaques were exposed to nursery reari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
(123 reference statements)
1
10
0
Order By: Relevance
“…23 These studies did not consider lineage (paternal grandparents or maternal grandparents) which have different influence on certain diseases. 24,25 In our study, based on the sufficiently large sample, we were able to distinguish grandparents between paternal and maternal lineage. Our results showed that a family history on either a paternal grandparent or a maternal grandparent with asthma was associated with an increased risk of childhood asthma, independent of parental asthma, although the impact on the asthma risk was less than a family history of a parent.…”
Section: Discussionmentioning
confidence: 87%
“…23 These studies did not consider lineage (paternal grandparents or maternal grandparents) which have different influence on certain diseases. 24,25 In our study, based on the sufficiently large sample, we were able to distinguish grandparents between paternal and maternal lineage. Our results showed that a family history on either a paternal grandparent or a maternal grandparent with asthma was associated with an increased risk of childhood asthma, independent of parental asthma, although the impact on the asthma risk was less than a family history of a parent.…”
Section: Discussionmentioning
confidence: 87%
“…However, prior studies using this model did not consider the possible non-genetic transmission of maltreatment-related phenotypes across generations and their relevance for disease risk. Importantly, models of ELS or early rearing experiences in NHP support the hypothesis that effects of nursery rearing, variable foraging demand stress, and variations in normal nurturing behavior, among others, may be transmitted across generations 6164 . Thus, we sought to use our ELS model with cross-fostering to examine the possibility of transmission of epigenetic risk in a well-controlled design.…”
Section: Introductionmentioning
confidence: 83%
“…Effects have been demonstrated in three generations, with paternal grandoffspring still showing these effects, and paternal great-grandoffspring showing only increased nervousness (Kinnally et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research with several species (including humans, rodents, and nonhuman primates) have shown that adverse early life experiences have transgenerational effects (e.g., Babb, Carini, Spears, & Nephew, ; Kundakovic & Champagne, ; Maestripieri, ). For example, offspring of nursery‐reared rhesus macaque males had elevated cortisol, lower immune cell counts, and increased emotionality compared to offspring of control males (Kinnally & Capitanio, ; Kinnally, Gonzalez, & Capitanio, ). Effects have been demonstrated in three generations, with paternal grandoffspring still showing these effects, and paternal great‐grandoffspring showing only increased nervousness (Kinnally et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation